The Abnormality of Spermatozoa Goat after Freezing on -80°C Using Tris Diluent Added Combination Hatching Egg Yolk and Amnion Fluid - Nisa, Liza Choirun; Rahayu, Sri; Ciptadi, Gatot (Graduate School, Universitas Brawijaya, 2018)
This study aims to determine the combination of the hatching egg yolk (HEY) and amniotic fluid (AF) in Tris diluent to the type of goat spermatozoa abnormalities after frozen at temperature -80°C. This study used four treatments and 6 replications. The semen is diluted using tris extender and added treatment, there are control group (T0) (Tris egg yolk 20%), T1 (15% HEY + 5% AF), T2 (10% HEY + 10% AF), and T3 (5% HEY + 15% AF). After dilution, the semen was equilibrated for 2 hours, then stored using Mr. Frosty and frozen at temperature -80°C in the ultra-freezer for 24 hours. The type of spermatozoa abnormalities type was evaluated on fresh semen and after thawing. The data were analyzed using ANOVA (P<0.05). The results showed that there is no significant difference among treatments. The primary abnormalities in fresh semen, there were macro-cephalic, amorphous, and the secondary spermatozoa abnormalities such as detached head, mid-piece defect, coiled tail, loosehead, shoe-hook tail, and a broken tail. The secondary abnormalities in post-thawing were found both in the control group and treatment, which are detached head, loosehead, coiled tail, shoe-hook tail, and broken tail. The conclusion of this study was the percentage of secondary abnormalities after thawing was increasing both in the control and treatment groups. Keywords: Amniotic Fluid, Hatching Egg Yolk, Mr. Frosty, Type of Spermatozoa Abnormality.